Ketidakpastian Lingkungan Bisnis, Keputusan Investasi dan Kinerja Perusahaan pada Industri Manufaktur - Dianwicaksih Arieftiara; Mariana Mariana (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2018)
This study aims to investigate the effect of environmental uncertainty as an antecedent to the relation of investment decision with firm’s performance. This study applies a comprehensive measure of environmental uncertaity. Using data from listed companies on Indonesian Stoct Exchange (IDX) for the period of 2009-2012, with purposive random sampling method and Two Stage Linear Regression (TSLS) method, this study found that the environmental uncertainty positively affects the managers’ investment decision. Moreover this study documented that the managers’ investment decisions, which taken by considering environmental uncertainty condition, increase the level of firm’s financial performance. This study provides empirical evidence of antecedence effect of environmental uncertainty on the relationship of investment decision and firms’ performance. The findings suggest that environmental uncertainty makes manager to take better investment decision, and it will eventually affect the firms’ performance.